Legacies of state violence and transitional justice in Latin America : a Janus-faced paradigm? - Schneider, Nina, 1980-; Esparza, Marcia (Lexington Books, 2015)
Legacies of State Violence and Transitional Justice in Latin America deconstructs the myth of unanimous support for the transitional justice paradigm across Latin America and conceptualizes transitional justice as a Janus-faced paradigm, as historically it has often hindered rather than advanced the quest for memory, truth, and justice. Based on local empirical evidence and including valuable voices from the Latin American Global South, this edited collection contradicts dominant assumptions in the much-cited international transitional justice literature.